Fighting Back against Antimicrobial Resistance with Comprehensive Policy and Education: A Narrative Review - Justin F. Hayes (MDPI AG, 2022)
Globally, antimicrobial resistance has emerged as a significant threat. A comprehensive plan is required to combat antimicrobial resistance. There have been national and international efforts to address this global health problem, but much work remains. Enhanced funding and regulations to support antimicrobial stewardship policy and program development, reforms to incentivize drug development to treat resistant pathogens, and efforts to strengthen One Health programs are areas for collaboration and innovation. Finally, implementation of educational interventions for trainees encompassing these key areas along with training on policy and leadership development is critical to enable sustainability of these efforts to fight back against antimicrobial resistance.